Caring for and being fair with data: Should we complement the FAIR principles with the CARE principles? - Marín-Arraiza, Paloma (Anuario ThinkEPI, 2023)
In recent years, the FAIR (Findable, Accessible, Interoperable, and Reusable) principles have been fully included in the technical dialogue on research data management, and parallel to them, the CARE (Collective Benefit, Authority to Control, Responsibility, Ethics) principles have also emerged. These focus on ethical and governance aspects, placing particular emphasis on indigenous data sovereignty. Unlike the FAIR principles, there are as yet no maturity or "CAREfication" models to assess the adoption of the CARE principles, and their implementation requires community development of services and data management. Despite the differences, an infrastructure that conforms to the FAIR principles can be more easily linked with the CARE principles. This work presents the CARE principles and their possible framing beyond technical management of research data.